Model Evaluasi Penerapan Good Farming Practice pada Peternakan Domba Di PT Tawakal Farm Bogor - Hasan, M. R. A.; Yamin, M.; Rahayu, S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
This research was aimed to evaluate Good Farming Practice (GFP) of sheep fattening at PT TF. The breed of sheep that are fattened in this farm are thin tailed and thick tailed. The aspects that evaluated were equipments aspect, production process, environmental conservation, and surveillance. The data were corrected by observation method and interview company leaders. Data were analyzed using descriptive analysis method with weighting based on importance aspect to GFP. The total GFP performance score were 81.90% indicated that the application of GFP PT TF was sufficiently good. The point of view from the aspect of production facilities and processes, PT TF has applied good GFP with the weighted value of each aspects were 82.13% and 85.25%, respectively.